The Role Of Nursing And Laboratory Professionals In Improving Screening Accessibility And Quality: A Systematic Review Of Saudi Arabia's Vision 2030 Implementation (The Review of Diabetic Studies, 2024)
BackgroundLaboratory technicians play a crucial role in advancing precision medicine by performing diagnostic tests, analyzing biomarkers, and interpreting results. Nursing technicians, also known as practical nurses or vocational nurses, are healthcare professionals who have completeda diploma or certificate program in nursing and are licensed to practice under the supervision of registered nurses. They perform various patient care tasks, such as measuring vital signs, administering medications, collecting specimens, and providing patient education. The Saudi Vision 2030 strategic plan aims to transform the healthcare system and improve population health outcomes through various initiatives, including expanding access to preventive services and enhancing the quality of screening programs. Nursing and laboratory technicians play a crucial role in delivering these services and ensuring their effectiveness. Laboratory testing plays a crucial role in the screening, diagnosis, and management of serving as the first step in identifying infected individuals and guiding treatment decisions.Aim of this systematically reviews: To the evidence on the role of nursing and laboratory technicians in improving screening accessibility and quality in Saudi Arabia, in the context of the Vision 2030 implementation.  Method: A comprehensive search of PubMed, CINAHL, Scopus, and Google Scholar databases was conducted for studies published between 2016 and 2024. These sources included online literature searches and other governmental health agencies.Results: database search yielded 120 records, of which 110 were duplicates and removed. After screening the titles and abstracts of the remaining records, excluded for not meeting the eligibility criteriaful , texts of the remaining 50 records reviewed, and 20 were further excluded for various reasons, such as not being conducted in Saudi Arabia, Conclusion:  The review highlights the need for strategic initiatives to build the capacity and competency of laboratory technicians and Nursing professionals in to establish standardized protocols and guidelines, and to foster a culture of innovation and continuous improvement in Saudi Arabian healthcare institutions . Further research is needed to evaluate the impact of laboratory technicians and nursing on patient outcomes, healthcare costs, and quality of care